Swiss Monitoring of Potential Organ Donors (SwissPOD): a prospective 12-month cohort study of all adult ICU deaths in Switzerland (Swiss Medical Weekly, 2014)
BACKGROUND: The Swiss Monitoring of Potential Organ Donors (SwissPOD) was initiated to investigate the causes of the overall low organ donation rate in Switzerland. The objective of our study was an assessment of the donation after brain death (DBD) process in Swiss adult intensive care units (ICUs), and to provide an overview of the donation efficiency as well as of the reasons for non-donation. METHODS: SwissPOD is a prospective cohort study of all deaths in Swiss ICUs and accident and emergency departments. This study is an analysis of SwissPOD data of all patients who deceased in an adult ICU between 1 September 2011 and 31 August 2012. RESULTS: Out of 3,667 patients who died in one of the 79 adult ICUs participating in SwissPOD, 1,204 were possible, 198 potential, 133 eligible, and 94 utilised DBD donors. The consent rate was 48.0% and the conversion rate 47.5%. In 80.0% of cases, the requests for donation took place before brain death was diagnosed, resulting in a similar proportion of consents and objections as when requests were made after brain death diagnosis. CONCLUSIONS: Despite the low donation rate, Swiss adult ICUs are performing well in terms of the conversion rate, similar to major European countries. The refusal rate is among the highest in Europe, which clearly has a negative impact on the donation rate. Optimising the request process seems to be the most effective means of increasing the donation rate.